Plant growth promotion induced by phosphate solubilizing endophytic Pseudomonas isolates - Otieno, Nicholas; Lally, Richard D.; Kiwanuka, Samuel; Lloyd, Andrew; Ryan, David; Germaine, Kieran J.; Dowling, David N. (Frontiers in Microbiology, 2015)
The use of plant growth promoting bacterial inoculants as live microbial biofertilisers provides a promising alternative to chemical fertilisers and pesticides. Inorganic phosphate solubilisation is one of the major mechanisms of plant growth promotion by plant associated bacteria. This involves bacteria releasing organic acids into the soil which solubilise the phosphate complexes converting them into ortho-phosphate which is available for plant up-take and utilisation. The study presented here describes the ability of endophytic bacterial isolates to produce gluconic acid, solubilise insoluble phosphate and stimulate the growth of Pea plants (Pisum sativum). This study also describes the genetic systems within three of these endophyte isolates thought to be responsible for their effective phosphate solubilising abilities. The results showed that many of the endophytic isolates produced gluconic acid (14-169 mM) and have moderate to high phosphate solubilisation capacities (~ 400-1300 mg L-1). When inoculated to Pea plants grown in sand/soil under soluble phosphate limiting conditions, the endophyte isolates that produced medium to high levels of gluconic acid also displayed enhanced plant growth promotion effects.